Is Being Competitive Always an Advantage? Degrees of Competitiveness, Gender, and Premature Work Contract Termination - Samuel Lüthi; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this study, we examine the influence of competitiveness on the stability of labour relations using the example of premature employment and training contract termination in the apprenticeship education sector. The paper extends the small but growing evidence on the external relevance of competitiveness by analysing gender differences in the correlation between competitiveness and labour market success and whether these effects depend on how the students' propensity to compete is measured. By matching a large experimental dataset with administrative data identifying contract terminations, we find that both gender and test specification matter. While competitive men assigned to a difficult competitiveness task are less likely to drop out of the contract than non competitive men, there is no such effect observable for those assigned to the easier task. On the other hand, competitive women are more likely to drop out than non competitive women, irrespective of how competitiveness is measured.
Keywords: C90; J16; J24; 330; competitiveness; non-cognitive skills; gender; apprenticeship